Urgensi Penataan Ulang Mekanisme Pengujian Peraturan Perundang-Undangan di Indonesia: (Analisis Normatif terhadap Kewenangan Lembaga Yudikatif) - Ismarini Della Purnama; Novaranty Zura Dwiputri; Wicipto Setiadi; Kaharuddin Kaharuddin (Pusat Riset dan Inovasi Nasional, 2024)
The current Indonesian legal system recognizes two paths of judicial review, although this division of authority is constitutionally legal, but in practice it raises serious problems. One of them is the inconsistency of decisions between judicial institutions. For example, there is a Supreme Court decision that cancels Regional Regulations that have previously been studied by the Constitutional Court, causing confusion in the application of the law. This not only weakens the principle of legal certainty, but also raises problems in the effectiveness of the judicial system. This study aims to identify the concept of restructuring the ideal regulatory testing mechanism according to the principle of the state of law and the theory of norm hierarchy and analyze the need for restructuring the regulatory testing mechanism in Indonesia from the perspective of legal certainty, justice, and law enforcement effectiveness. The research method used in this study is normative juridical and uses a legislative approach. The results of the study show.